The Wolf King : Ibn Mardanish and the Construction of Power in al-Andalus - Balbale, Abigail Krasner (Book collections on Project MUSE., 2022)
"Draws on methodologies from history, philology, and art history to examine chronicles, chancery documents, poetry, architecture, coins, and portable objects to reveal how Muhammad ibn Sa'd ibn Mardanīsh, celebrated in Castilian and Latin sources as the Wolf King, adapted language and forms from around the Islamic world to construct power"--